Analysis of Factors Influencing the Selection of Contraceptive Methods in Women of Reproductive Age - Purwanti, Anik; Latifah, Ade Ifah (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: Only 19% of women of reproductive age in Indonesia use long-term contraceptive methods, with injectable birth control being the most frequently used method at 43.5%. A comprehensive understanding of the factors that influence contraceptive selection is essential for designing effective family planning programs and improving the reproductive health of women of reproductive age. This study aims to identify the factors that affect the selection of contraceptive methods among women of reproductive age in Cikunir Village, Tasikmalaya.Subjects and Method: This study uses an observational analytical design with a cross-sectional study. This research was conducted in Cikunir Village, Tasikmalaya. Samples were taken using purposive sampling techniques, consisting of 153 women of reproductive age (15-44 years) who had more than two children and had no contraindications to birth control. The dependent variable was use of contraceptives. The independent variables were demographic, socio-economic, knowledge, attitudes, accessibility of health services, and the role of health workers. Data collection using a primary questionnaire that had been validated and tested for reliability. Data analysis using chi-square tests and multivariate logistic regressionResults: Knowledge (OR=15.08; 95% CI=5.11 to 44.48; p<0.001), husband's support (OR=7.94; 95% CI=2.95 to 21.35; p<0.001), high income (OR=5.50; 95% CI=1.80 to 16.74; p=0.003), and parity (OR= 3.33; 95% CI=1.20 to 9.20; p=0.020) increased the likelihood of contraceptive use. Conclusion: The factors that affect the choice of contraceptive use in women of reproductive age in Cikunir Village are knowledge, husband's support, high income, and parity.